COL8A1 overexpression promotes glioma cell growth by activating focal adhesion kinase signaling cascade - Jin Qian; Haihui Xing; Yin Wang; Chen Li; Hairong Chen; Jun Rong; Chunfa Qian (npj Precision Oncology)
Abstract We explored expression and biological roles of collagen type VIII alpha-1 chain (COL8A1) in glioma. Bioinformatics analyses unveiled COL8A1 overexpression within glioma tissues correlates with adverse clinical outcomes of patients. COL8A1 overexpression was also detected in local glioma tissues and various glioma cells. In primary and immortalized glioma cells, COL8A1 shRNA or knockout (KO) reduced cell viability, proliferation and mobility, disrupted cell cycle, and prompted apoptosis. While COL8A1 overexpression augmented the malignant behaviors in glioma cells. COL8A1 shRNA or KO in primary glioma cells decreased phosphorylation of FAK and downstream targets Akt and Erk1/2. Conversely, elevating COL8A1 expression increased their phosphorylations. In vivo experiments confirmed growth inhibition of patient-derived glioma xenografts within the mouse brain following COL8A1 KO. Hindered proliferation, lowered phosphorylation levels of FAK, Akt, and Erk1/2, as well as increased apoptosis were observed within the COL8A1 KO intracranial glioma xenografts. Thus, COL8A1 overexpression promotes glioma cell growth.